PENGARUH HARGA MINYAK DUNIA DAN SUKU BUNGA BI TERHADAP HARGA SAHAM PERTAMBANGAN JANUARI PERIODE 2006-JULI 2008 - Anisa Iswandari; Nazaruddin Malik (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
The purpose of this research has done to knowing crude oil price dan BI rate to stock price on mining. The hypothesis are guess that crude oil price influence to stock mining and BI rate influence to stock mining. Analysis instrument to knowing influence of crude oil price and BI rate is use multiple linier regression analysis. To know what is the reach of independent variable influence to dependent variable use a hypothesis testing with a partial test (t test), simultant test (f test) and to knowing how the independent variable representative to dependent variable use a godness of fit (R2). The results of hypothesis analysis shows that crude oil price and BI rate have a significant influence to stock mining. Proof from the results shows that F test 259,5605 > F table 3,32. Partial test shows that crude oil price positive influence to mining which t test > t table (9,446>2,045) and BI rate not influence to mining which t test < t table (-12,008<2,045) with level a significant 5%.